Adoption of the ISA 500 and its Impact on Audit Quality and Fraud Reduction: Evidence from Iraq - Wahhab, Asaad; Ibrahim Obaid, Amna (Technium Social Sciences Journal, 2023)
This study aims to demonstrate how adopting the international auditing standard 500 will improve audit quality in audit agencies. The Financial Supervision Bureau auditors and the possibility of benefiting from the research results prompted a recommendation to the Auditor Profession Council to adopt the two international standards of evidence and to accomplish the study's objective; the Auditor Profession Council has adopted these standards. A questionnaire form was adopted for this purpose, and 100 questionnaires were distributed to a sample of auditors in Iraqi auditing agencies and 100 questionnaires to auditors in the Federal Financial Supervision Bureau. All 200 distributed questionnaires were retrieved, and the data were analyzed using the statistical analysis programs SPSS 23 and Amos to test hypotheses based on the path analysis model. The research concluded that the Iraqi Accounting and Supervisory Standards Board must adopt International Auditing Standard 500 due to the impact of this standard on audit quality and fraud reduction.